Measuring risk and efficiency for some Islamic banks in Kuwait: قياس المخاطر والكفاءة لبعض البنوك الإسلامية في الكويت (المجلة العربية للعلوم و نشر الأبحاث, 2017)
This study measures risk and efficiency in selected sample of Islamic banks in Kuwait using financial ratio analysis during the period (2010-2014) in order to find relationship between risk and operation efficiency in the mentioned sample. We used three stages of analysis in this paper, first phase included the measurement of the efficiency of these banks through the financial ratios related to operational efficiency analysis, while the second phase involves the analysis of credit risk ratios, liquidity and operational risk, and in the third stage I studied the relationship between these risks and its impact on the financial and operational efficiency. It has been introduced analytical tables showing the relationship between efficiency and risk of four Islamic banks in Kuwait. The overall results of this paper was that the operational efficiency of these banks are affected directly proportional to credit risk, and inversely to liquidity risk, while there is no clear relationship between operational efficiency and operational risk